3D printing polycaprolactone micro-nano copper scaffolds with a high antibacterial performance for potential sewage treatment. (February 2022) - Wang, Zhilong; Han, Zongpu; Liao, Xiaozhu; Zhang, Xiao; Liang, Jiachen; Xing, Zhe; Fan, Zengjie
Effective application of micro-nano copper particles in elimination of the pathogenic microorganisms in the water remains a challenge. In this study, an optimum structural design was adopted in mathematical models to improve the efficiency of sewage filtration, and polycaprolactone/copper scaffold (PCs) was fabricated through a 3D printing method. The result shows that the micro-nano copper particles were physically embedded into the polycaprolactone scaffolds. In addition, the antibacterial efficiency of PCs against E. coli and S. aureus was up to 100% and the antibacterial performance could be remained in sewage filtration (copper: polycaprolactone = 1:2). The results suggest that PCs is a good candidate for application in the sewage treatment.